Odpowiedzi

Najlepsza Odpowiedź!
2010-04-16T12:51:52+02:00
A) a=b+c
a-b=c
c=a-b

a=b+c
a-c=b
b=a-c

B) a=bc-d
a-bc=-d |*(-1)
d=bc-a

a=bc-d
a+d=bc
bc=a+d |:c
b=(a+d):c

a=bc-d
a+d=bc
bc=a+d |:b
c=(a+d)/b

C) a=bc+d
-d=-a+bc |*(-1)
d=a-bc

a=bc+d
a-d=bc
bc=a-d |:b
c=a-d)/b

a=bc+d
a-d=bc
bc=a-d |:c
b=(a-d)/c

D) a=b(c+d) |:b
a/b=c+d
a/b-c=d
d=a/b-c

a=b(c+d) |:b
a/b=c+d
a/b-d=c
c=a/b-d

a=b(c+d) |:(c+d)
a/(c+d)=b
b=a/(c+d)

E) a=b+c nad d
a=b+c/d
a-c/d=b
b=a-c/d

a=b+c/d
a-b=c/d |*d
(a-b)*d=c
c=(a-b)*d

a=b+c/d |*d
ad=bd+c
ad-bd=c
d(a-b)=c |:(a-b)
d=c/(a-b)

F) a=b-c nad d
a=b-c/d
a+c/d=b
b=a+c/d

a=b-c/d
a-b=-c/d |*(-d)
(a-b)*(-d)=c
c=(a-b)*(-d)

a=b-c/d
a-b=-c/d |*d
ad-bd=-c
d(a-b)=-c |:(a-b)
d=-c/(a-b)

G) a=b nad c+d
a=b/(c+d) |*(c+d)
a*(c+d)=b
b=a*(c+d)

a=b/(c+d) |*(c+d)
a*(c+d)=b |:a
c+d=b/a
c=b/a-d

a=b/(c+d) |*(c+d)
a*(c+d)=b |:a
c+d=b/a
d=b/a-c

H) a=b nad c-d
a=b/(c-d) |*(c-d)
a*(c-d)=b
b=a*(c-d)

a=b/(c-d) |*(c-d)
a*(c-d)=b |:a
c-d=b/a
c=b/a+d

a=b/(c-d) |*(c-d)
a*(c-d)=b |:a
c-d=b/a
-d=b/a-c |*(-1)
d=-b/a+c

I) a=b/c + d
a-d=b/c |*c
(a-d)*c=b
b=(a-d)*c

a=b/c+d
a-d=b/c
-d=b/c-a |*(-1)
d=-b/c+a

a=b/c+d
a-d=b/c |*c
ac-dc=b
c(a-d)=b |:(a-d)
c=b/(a-d)